A STUDY ON HOW THE REGIONAL FINANCIAL INDEPENDENCE RATIO SUPPORTS REGIONAL AUTONOMY IN SERANG CITY - Tejaarief, Billy; Husni, Mohamad (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Regional financial independence covers the region's capacity to oversee and make use of its financial resources effectively and efficiently, without reliance entirely on the funds of the central government in accordance with Act No. 32 of 2004 on regional government. This study aims to find out how great the degree of economic independence of the local government is, in particular the Kota Serang, in support of the autonomy of the area. This research uses the method of descriptive with a qualitative approach by measuring the ratio of financial independence of the government of the area of Kota Serang. The data obtained through observations and library studies were used for data analysis techniques using the ratio of regional financial independence (RKKD). The results of the research showed that the ratios of financial autonomy of the Kota Serang during the period 2021–2023 are still at a low level, i.e., at 35.04%. It can be understood that the real income of the Kota Serang still relies on the contributions of either the Central Government or the Provincial Government through the General Allocation Fund and Special Allocation Funds. Keywords: Regional Natural Income; Ratio of Financial Independence; Regional Financial Management